A rare case of extensive cranial Langerhans cell histiocytosis, synchronously presenting as otitis externa and giant cell arteritis. (11th November 2016) - Darr, Adnan; Mughal, Zahir; Martin, Thomas
Abstract: Langerhans cell histiocytosis (LCH) is a rare histiocytic disorder of unpredictable clinical course and varied modes of presentation. The spectrum of presentation is wide, ranging from isolated eosinophilic granulomas to multiple lesions and diffuse systemic involvement. We present the case of a 52-year-old man, who presented with an 8-week history of worsening otalgia and superficial temporal tenderness attributed to otitis externa within the community and subsequently giant cell arteritis. Computed tomography and magnetic resonance imaging were undertaken due to atypical features, which demonstrated bony destruction within the right greater wing of the sphenoid, squamous part of temporal and mastoid bone, with middle cranial fossa communication. Intra-orbital extension was noted with abutment of the lateral rectus muscle. Mastoid biopsies demonstrated a mixture of lymphocytes, eosinophils and monomorphic epithelial cells with pale cytoplasm and focal areas of granulation tissue/necrosis. The features were consistent with a diagnosis of LCH, and the patient was subsequently transferred to a tertiary centre for definitive treatment.